Functional disorders of speech and hearing in a south Indian general hospital - Kameswaran S (Journal of All India Institute of Speech and Hearing, 1972)
The child guidance clinics often receive patients with stammering. Thesepatients, generally, come after all the available medical examinations have beentried. This is because in our country, such a problem is supposed to be a medicalsubject. When such cases are received it becomes easier to look for the causes ofstammering. The factors contributing and precipitating lie mostly in the child'ssocio-emotional spheres.